Nidogen‐1 Mitigates Ischemia and Promotes Tissue Survival and Regeneration. Issue 4 (21st December 2020) - Zbinden, Aline; Layland, Shannon L.; Urbanczyk, Max; Carvajal Berrio, Daniel A.; Marzi, Julia; Zauner, Monika; Hammerschmidt, Anne; Brauchle, Eva M.; Sudrow, Katrin; Fink, Simon; Templin, Markus; Liebscher, Simone; et al.
Abstract: Ischemia impacts multiple organ systems and is the major cause of morbidity and mortality in the developed world. Ischemia disrupts tissue homeostasis, driving cell death, and damages tissue structure integrity. Strategies to heal organs, like the infarcted heart, or to replace cells, as done in pancreatic islet β ‐cell transplantations, are often hindered by ischemic conditions. Here, it is discovered that the basement membrane glycoprotein nidogen‐1 attenuates the apoptotic effect of hypoxia in cardiomyocytes and pancreatic β ‐cells via the α v β 3 integrin and beneficially modulates immune responses in vitro. It is shown that nidogen‐1 significantly increases heart function and angiogenesis, while reducing fibrosis, in a mouse postmyocardial infarction model. These results demonstrate the protective and regenerative potential of nidogen‐1 in ischemic conditions. Abstract : Nidogen‐1 functionalized gels increase cell and tissue survival and function in ischemic conditions via a synergic combination of improved angiogenesis, cell protection, immunomodulation, and reduced fibrosis. A preclinical mouse model of myocardial infarction shows an increase in heart function and demonstrates the clinical potential of a Nidogen‐1 as an off‐the‐shelf therapy.